Predictors of Cell-Associated Human Immunodeficiency Virus (HIV)-1 DNA Over 1 Year in Very Early Treated Infants. (29th June 2021) - Kuhn, Louise; Paximadis, Maria; Da Costa Dias, Bianca; Shen, Yanhan; Mncube, Sizanani; Strehlau, Renate; Shiau, Stephanie; Patel, Faeezah; Burke, Megan; Technau, Karl-Günter; Sherman, Gayle; Loubser, Shayne; et al.
Abstract: Background: Younger age of antiretroviral therapy (ART) initiation is associated with smaller viral reservoirs in perinatally acquired HIV-1 infection, but there is wide variability among early-treated infants. Predictors of this variability are not fully described. Methods: Sixty-three neonates diagnosed with HIV-1 <48 hours after birth in Johannesburg, South Africa, were started on ART as soon as possible. Fifty-nine (94%) infants received nevirapine prophylaxis from birth until ART start. Viably preserved peripheral blood mononuclear cells (PBMCs) collected at regular intervals to 48 weeks, and from mothers at enrollment, were tested using integrase-targeted, semi-nested, real-time quantitative hydrolysis probe (TaqMan) PCR assays to quantify total HIV-1 subtype C viral DNA (vDNA). Predictors were investigated using generalized estimating equation regression. Results: Thirty-one (49.2%) infants initiated ART <48 hours, 24 (38.1%) <14 days, and 8 (12.7%) >14 days of birth. Three-quarters were infected despite maternal antenatal ART (however, only 9.5% of women had undetectable viral load closest to delivery) and 86% were breastfed. Higher infant CD4+ T-cell percentage and viral load <100 000 copies/mL pre-ART were associated with lower vDNA in the first 48 weeks after ART start. No antenatal maternal ART and breastfeeding were also associated with lower vDNA. Older age at ART initiation had a discernible negative impact when initiated >14 days. Conclusions: Among very early treated infants, higher CD4+ T-cell percentage and viral load <100 000 copies/mL pre-ART, infection occurring in the absence of maternal antenatal ART, and breastfeeding were associated with lower levels of HIV-1 DNA in the first 48 weeks of treatment. Clinical Trials Registration. clinicaltrials.gov (NCT02431975). Abstract : Initiation of antiretroviral therapy in the first 2 weeks of life, higher CD4+ T-cell percentage and viral load <100 000 copies/mL pre–antiretroviral therapy (-ART), no maternal antenatal ART, and breastfeeding were associated with smaller persisting viral reservoir in infants.